Problems of internal audit in Ukraine - Letucha, Anna (My University, 2014)
In the current financial and economic crisis large enterprises need to implement a set of measures on improvement of their activities to maintain market competitiveness and increase profitability. В умовах нинішньої фінансово-економічної кризи великі підприємства необхідно здійснити комплекс заходів щодо поліпшення їх діяльності для підтримки конкурентоспроможності на ринку і підвищити прибутковість.
Keywords: internal audit; economic crisis; внутрішня ревізія; економічна криза